Historical-juridical and economic perspective if the publicans´companies like generating instruments of markets of the financial capitals of corporate debt (public and private) and shares in classical Rome - Blázquez, Guillermo Suárez (Revista Jurídica Portucalense, 2016)
Our study directs to be analyzed, from a perspective historical - juridical and economic, to the publicans' companies as juridical creative entities of corporate financial debt in the Classic Rome